Peran Advokat dalam Perlindungan Hak Korban Pemerkosaan dalam Sistem Peradilan di Indonesia - Faidhul Rasyid; Reza Fitri Ananda (Lembaga Pengembangan Kinerja Dosen, 2026)
Protection of rape victims’ rights within the Indonesian criminal justice system continues to face significant challenges, particularly regarding the role of advocates, who have traditionally focused more on assisting suspects or defendants. This study aims to analyze and describe the role of advocates in protecting the rights of rape victims, including the rights to legal assistance, restitution, and physical as well as psychological recovery. The research employs a normative juridical approach through the analysis of statutory regulations and relevant legal literature. The findings reveal that the role of advocates in assisting rape victims remains limited due to the absence of explicit provisions in the Indonesian Criminal Procedure Code (KUHAP) granting advocates full authority to represent victims throughout all stages of criminal proceedings. Consequently, victims frequently encounter obstacles in accessing justice and obtaining adequate legal protection. This condition demonstrates the need for legal reform to strengthen the position and authority of advocates in representing victims within the criminal justice process. Strengthening the role of advocates is expected to improve legal protection, ensure the fulfillment of victims’ rights, and support the recovery process for rape victims in Indonesia.